Outcomes of pre-operative brachytherapy followed by hysterectomy for early cervical cancer. Issue 2 (22nd December 2019) - Bataille, Benoit; Escande, Alexandre; Le Tinier, Florence; Parent, Audrey; Bogart, Emilie; Collinet, Pierre; Bresson, Lucie; Narducci, Fabrice; Leblanc, Eric; Lemaire, Anne-Sophie; Taieb, Sophie; Lartigau, Eric; et al.
Abstract : Objective: The standard of care for early cervical cancer is radical hysterectomy; however, consideration of pre-operative brachytherapy has been explored. We report our experience using pre-operative brachytherapy plus Wertheim-type hysterectomy to treat early stage cervical cancer. Methods: This single-center study evaluated consecutive patients with histologically proven node-negative early stage cervical cancer (International Federation of Gynecology and Obstetrics 2009 stage IB1–IIB) that was treated using pre-operative brachytherapy and hysterectomy. Pre-brachytherapy staging was performed using magnetic resonance imaging (MRI) and pelvic lymph node assessment was performed using lymphadenectomy. The tumor and cervical tissues were treated using brachytherapy (total dose 60 Gy) followed by Wertheim-type hysterectomy. The study included patients from January 2000 to December 2013. Results: A total of 80 patients completed a median follow-up of 6.7 years (range 5.4–8.5). The surgical specimens revealed a pathological complete response for 61 patients (76%). Patients with incomplete responses generally had less than 1 cm residual tumor at the cervix, and only one patient had lymphovascular space involvement. The estimated 5-year rates were 88% for overall survival (95% CI 78% to 94%) and 82% for disease-free survival (95% CI 71% to 89%). Toxicities were generally mild-to-moderate, including 26 cases (33%) of grade 2 late toxicity and 10 cases (13%) of grade 3 late toxicity. Univariate analyses revealed that poor disease-free survival was associated with overweight status (≥25 kg/m 2, HR 3.05, 95% CI 1.20 to 7.76, p=0.019) and MRI tumor size >3 cm (HR 3.05, 95% CI 1.23 to 7.51, p=0.016). Conclusions: Pre-operative brachytherapy followed by Wertheim-type hysterectomy may be safe and effective for early stage cervical cancer, although poorer outcomes were associated with overweight status and MRI tumor size >3 cm.